A proposal towards a single title: an overview on Malaysian National Land Code 1965 - Sufian, Azlinor; Mohamad, Nor Asiah; Mohamad, Mazliza (Conference Master Resources, 2013)
Malaysia is moving towards improving its land administration delivery system by implementing electronic conveyancing. This is evident through the submission of a proposal paper forwarded by the Department of Director of Land and Mines, Ministry of Natural Resources and Environment. One of the proposals is concerning the implementation one title system as a path to assist the implementation of electronic land administration system. The proposal was made based on the view that the existing system of having two titles at Registry Title Office and District Land Office level has created numerous land Registers database at State level. This paper is prepared based on the qualitative research methodology. The paper is aimed to analys the viability of implementing one single title and its relation to the Computerised Land Registration System and E-Alienation